The Effect Of Leverage, Company Size, Inflation Rate, And Cash Holding On Company Value (In Hotel, Restaurant, and Tourism Sub-Sector Companies Listed on the IDX for the 2017-2020 period) - Wirdayanti Wirdayanti; Reniati Reniati; Darman Saputra (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to determine the effect of leverage, firm size, inflation rate, and cash Holding on firm value (in hotel, restaurant, and tourism Sub-Sector companies Listed on the Indonesian Stock Exchange for the 2017-2020 period). This research is a type of quantitative research. The population in this study amounted to 35 companies, using purposive sampling technique, obtained a research sample of 18 companies. The analytical method used in this research is multiple linier regression. The result showed that : (1) Leverage had a negative and significant effect on firm value. (2) Firm size has a negative and significant effect on firm value. (3) Inflation rate has no effect on firm value. (4) Cash Holding has a positive and significant effect on firm value. Keywords : Leverage (DER), Company Size, Inflation Rate, Cash Holding, and Company Value (PBB)